Performance Analysis of a High-Order Discontinuous Galerkin Method Application to the Reverse Time Migration (Communications in Computational Physics, 2020)
This work pertains to numerical aspects of a finite element method baseddiscontinuous functions. Our study focuses on the Interior Penalty DiscontinuousGalerkin method (IPDGM) because of its high-level of flexibility for solving the fullwave equation in heterogeneous media. We assess the performance of IPDGM througha comparison study with a spectral element method (SEM). We show that IPDGM isas accurate as SEM. In addition, we illustrate the efficiency of IPDGM when employedin a seismic imaging process by considering two-dimensional problems involving theReverse Time Migration.